Handbook of youth prevention science - Doll, Beth, 1952-; Pfohl, William; Yoon, Jina.; T&F eBooks (New York : Routledge, 2010)
"Prevention research has traditionally focused on preventive interventions tied to specific disorders, e.g., substance abuse, conduct disorders, or criminality. This produced "silos" of isolated knowledge about the prevention of individual disorders but not about interventions that work across disorders. This handbook is the first to comprehensively describe current research and practice in mental health prevention programs that is organized around comprehensive prevention systems that reach across all disorders and all institutions within a community. Throughout the book preventive interventions are seen as a necessary component of effective mental health programs, not as a replacement for therapeutic interventions"--Provided by publisher.
12. Development, evaluation, and diffusion of a national anti-bullyiong program, KiVa -- 13. Promoting the well-being of school communities : a systemic approach -- 14. Promoting student resilience : strong kids social and emotional learning curricula -- 15. Stimulating positive social interaction : what can we learn from TIGER (Kanjertraining)? -- 16. A hybrid framework for intervention development : social justice for bullying in low-resource schools -- 17. Check & connect : enhancing school completion through student engagement -- 18. Prevention and early intervention for preschool children at risk for learning and behavior problems -- 19. Partnering to achieve school success : a collaboration care model of early intervention for attention and behavior problems in urban contexts -- 20. Dissemination of evidence-based programs in the schools : the coping power program -- 21. Prevention, early childhood intervention, and implementation science -- 22. Taking effective prevention to scale -- 23. Youth policy and politics in the United States : toward an increased focus on prevention.
Includes bibliographical references and index.
Also available in print edition.
Mode of access: World Wide Web.
Keywords: School mental health services; School children -- Mental health services; Problem children -- Education; Child psychology; Educational counseling; Electronic books